The Opinions of Afghan Uzbek Turks that are Learning Turkish as a Foreign Language on Turkish - Şengül, Kübra (Fırat University, 2017)
When viewing the Turkish learners who study Turkish as a foreign language, it is seen that majority of them consist of Turkish ancestors. Therefor, the reason for their learning Turkish and the difficulties encountered during the learning process of Turkish and the investigation of the views on Turkish, will provide a realistic and a demanding Schedule. The purpose of this researchis to determine the opinions of Afghan Uzbek Turks on Turkish spoken in Turkey. In this study, which is designed by qualitative research, semi-structured interview form was used as a data collection tool. According to the results of research, it is determined that the students have a particular tendency towards Turkey and Turkish spoken in Turkey and this stiuation results form the historical, politicalfriendship, smilarity of language, religion and culture with the family support.

Türkçeyi yabancı bir dil olarak öğrenenlere bakıldığında bunların büyük bir çoğunluğunu Türk soyluların oluşturduğu görülmektedir. Dolayısıyla Türk soyluların, Türkiye Türkçesini öğrenme sebeplerinin, Türkçe öğrenme süreçlerinde karşılaştıkları sorunların ve Türkçeye yönelik görüşlerinin araştırılması alanın daha gerçekçi ve ihtiyaca yönelik planlanmasını sağlayacaktır. Bu araştırmanın amacı da, Afganistanlı Özbek Türklerinin Türkiye Türkçesine ve bununla da ilişkili olarak Türkiye’ye yönelik görüşlerini belirlemektir. Nitel araştırma modeline göre tasarlanan çalışmada veri toplama aracı olarak yarı yapılandırılmış görüşme formu kullanılmıştır. Araştırma sonuçlarına göre öğrencilerin Türkiye’ye ve Türkiye Türkçesine yönelik özel bir eğilimlerinin olduğu, bu durumun da Afganistan ile Türkiye arasındaki tarihî ve siyasi dostluk, din, dil, kültür benzerliği ile aile desteğinden kaynaklandığı belirlenmiştir.
YABANCI DİL OLARAK TÜRKÇE ÖĞRENEN AFGANİSTANLI ÖZBEK TÜRKLERİNİN TÜRKİYE TÜRKÇESİNE YÖNELİK GÖRÜŞLERİ